How Important Is Meltwater to the Chamkhar Chhu Headwaters of the Brahmaputra River? - Hill, Alice F.; Rittger, Karl; Dendup, Tshewang; Tshering, Dendup; Painter, Thomas H. (Frontiers in Earth Science, 2020)
As our global climate warms, people and economies utilizing water resources sourced by snow and ice melt in mountain areas are disproportionately affected relative to locations that rely on rainfall. Worldwide, the vast majority of those impacted by snowfall changing to rainfall and earlier melt from a warming climate live in Asia. The Brahmaputra River originates in the declining glaciers and snowfields of the Chinese and Bhutanese Himalaya before flowing to the mega population centers of the Bangladesh delta. Bhutan’s economy relies on water resource-dependent hydropower and agriculture imposing important questions about the impact of climate change on the long-term viability of these important economic sectors. To clarify potential effects on water supplies in a warming world, and specifically to quantify the role of meltwater to river discharge in the headwaters of the Brahmaputra basin, we utilize a combined field observation-remote sensing approach to quantify river discharge source waters in a representative headwater basin, the Chamkhar Chhu. Using four years of water isotope and chemistry data together with a Bayesian Monte Carlo mixing model run seasonally in 2016, we find that the Chamkhar Chhu is mostly a rain-dominated basin at the lower elevation of our study domain (2591 m a.s.l.), with peak contributions from snowmelt in the early-monsoon and ice melt in the post-monsoon seasons. The radioactive tritium isotope shows glacier ice at the terminus was formed before the 1960s bomb spike while late monsoon groundwater and river water samples are sourced from mostly newer water inputs. An overall decreasing trend in the minimum snow and ice cover extent maps produced using MODIS Terra data from 2000-2017 suggest a lessening of cryospheric water resource availability in the basin, although this time series is short compared to the timescale of atmospheric-oceanic oscillations controlling snowfall. While decreasing snow and ice resources will likely lead to changing melt water contributions to river discharge, the overall impact on the water resources may be buffered by rainfall contributions as previous studies forecast an increase in precipitation for the region that will likely make up for lower melt water inputs.